2015
DOI: 10.1038/nmeth.3543
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRscan: designing highly efficient sgRNAs for CRISPR-Cas9 targeting in vivo

Abstract: CRISPR/Cas9 technology provides a powerful system for genome engineering. However, variable activity across different single guide RNAs (sgRNAs) remains a significant limitation. We have analyzed the molecular features that influence sgRNA stability, activity and loading into Cas9 in vivo. We observe that guanine enrichment and adenine depletion increase sgRNA stability and activity, while loading, nucleosome positioning and Cas9 off-target binding are not major determinants. We additionally identified truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,071
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,113 publications
(1,109 citation statements)
references
References 51 publications
35
1,071
2
1
Order By: Relevance
“…In particular, knockin efficiency depends critically on the activity of the sgRNA used for genomic cleavage. Different sgRNA sequences can vary widely in term of potency, and prediction algorithms have been developed to overcome this issue (37,38). However, because HDR knockin requires genomic cleavage close to the site of tag integration, for some genes the choice of sgRNAs to pick from might be scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, knockin efficiency depends critically on the activity of the sgRNA used for genomic cleavage. Different sgRNA sequences can vary widely in term of potency, and prediction algorithms have been developed to overcome this issue (37,38). However, because HDR knockin requires genomic cleavage close to the site of tag integration, for some genes the choice of sgRNAs to pick from might be scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The online CRISPRscan tool was used to design gRNAs targeting the zebrafish 3' UTR region in the rab13 locus (Moreno-Mateos et al, 2015). Oligonucleotides comprising the target sequences flanked by the T7 promoter and the Tail annealing sequence (Moreno-Mateos et al, 2015) were annealed to the Tail primer in a T100 thermal cycler (BioRad).…”
Section: Grna Generation and In Vitro Translationmentioning
confidence: 99%
“…Oligonucleotides comprising the target sequences flanked by the T7 promoter and the Tail annealing sequence (Moreno-Mateos et al, 2015) were annealed to the Tail primer in a T100 thermal cycler (BioRad).…”
Section: Grna Generation and In Vitro Translationmentioning
confidence: 99%
“…This may indicate that the sequence context of the targeted site can be a determinant of either the repair mechanism [131] induced by the DNA nick or the activity of the guide. The latter has been demonstrated to be affected by the sequence content [210]. Furthermore, although the Merkle et al [145] study reported a total mean indel frequency for Cas9WT that is higher than Cas9n (10-fold difference for the untargeted allele), the distribution pattern of the data was similar.…”
Section: Screening For the Presence Of Random Integrationsmentioning
confidence: 89%
“…The difference in mutagenic activity of Cas9WT associated with a given guide sequence has been the subject of intense study [91,210,230,231]. Various factors influence nuclease activity such as sgRNA characteristics, Cas9 protein characteristics, and the locus context of the target DNA sequence in the cell type under study.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%